Dogs don't tell jokes - Sachar, Louis, 1954- (New York : Knopf, 1991)
Twelve-year-old Gary, known as Goon because of his constant clowning and joke-telling, tries to change his image and make new friends at school.
G2
Keywords: Self-perception -- Fiction; Schools -- Fiction